Southern African Origin of HTLV-1 in Romania. - Olivier Cassar; Ambroise Marçais; Olivier Hermine; Emilie Deruelle; Giovanni Begliomini; Alexandru Bardas; Horia Bumbea; Andrei Colita; Daniel Coriu; Viola Maria Popov; Alina Tanase; Philippe Vicente Afonso; et al. (Public Library of Science (PLoS), 2024)
In Europe, most HTLV-1-infected individuals originate from highly endemic regions such as West Indies, sub-Saharan Africa, and South America. The only genuine endemic region for HTLV-1 in Europe is Romania where ATL series have been reported among Romanian patients. Our objective is to better understand the origin of this endemic focus based on a study of the genetic diversity of HTLV-1 in Romanians. DNA was obtained from PBMCs/buffy coats of 11 unrelated HTLV-1-infected individuals of Romanian origin. They include 9 ATL cases and 2 asymptomatic carriers. LTR sequences were obtained for all specimens. Complete genomic HTLV-1 sequences were obtained using four PCR series on 10 specimens. Phylogenetic trees were generated from multiple alignments using HTLV-1 prototypic sequences and the new generated sequences. Most of the complete LTR sequences (756-bp) showed low nucleotide diversity, ranging from 0% to 0.8% difference, and were closely related (less than 0.8% divergence) to the only previously characterized Romanian strain, RKI2. One strain, ROU7, diverged slightly (1.5% on average) from the others. Phylogenetic analyses both on partial LTR and the complete genome demonstrate that the 11 sequences belong to the HTLV-1a cosmopolitan genotype and 10 of them belong to the previously denominated a-TC Mozambique-Southern Africa A subgroup. In this study, we demonstrated that the HTLV-1 present in Romania most probably originated in Southern Africa. As most Romanian HTLV-1 strains are very closely related, we can assume that HTLV-1 has been introduced into the Romanian population recently. Further studies are ongoing to decipher the routes of arrival and dissemination of these HTLV-1 strains, and to date the emergence of this endemic focus in Central Europe.